Screenomics: A New Approach for Observing and Studying Individuals' Digital Lives. Issue 1 (January 2020) - Ram, Nilam; Yang, Xiao; Cho, Mu-Jung; Brinberg, Miriam; Muirhead, Fiona; Reeves, Byron; Robinson, Thomas N.
This study describes when and how adolescents engage with their fast-moving and dynamic digital environment as they go about their daily lives. We illustrate a new approach— screenomics —for capturing, visualizing, and analyzing screenomes, the record of individuals' day-to-day digital experiences. Sample includes over 500, 000 smartphone screenshots provided by four Latino/Hispanic youth, age 14 to 15 years, from low-income, racial/ethnic minority neighborhoods. Screenomes collected from smartphones for 1 to 3 months, as sequences of smartphone screenshots obtained every 5 seconds that the device is activated, are analyzed using computational machinery for processing images and text, machine learning algorithms, human labeling, and qualitative inquiry. Adolescents' digital lives differ substantially across persons, days, hours, and minutes. Screenomes highlight the extent of switching among multiple applications, and how each adolescent is exposed to different content at different times for different durations—with apps, food-related content, and sentiment as illustrative examples. We propose that the screenome provides the fine granularity of data needed to study individuals' digital lives, for testing existing theories about media use, and for generation of new theory about the interplay between digital media and development.